Minimum Inhibitory And Fungicidal Concentrations For Combined Extracts Of Papaya Leaves And Garlic - Siti Rusdiana Puspa Dewi; Pudji Handayani; Anita Nurmilasari; Rahmatullah Irfani; Tyas Hestiningsih; Ade Puspa Sari (Dentistry Study Program, Faculty of Medicine Universitas Sriwijaya, 2026)
Introduction: Oral Candidiasis is a common fungal infection caused by Candida albicans-a predominant cause of fungal infections in the oral cavity. Prolonged use of antifungal agents for oral candidiasis can be associated with side effects, indicating a need to consider alternative therapies. Natural resources such as papaya leaves and garlic have the effect of antifungal against Candida albicans that may serve as alternative therapies. In vitro study of the minimum inhibition and fungicidal concentration of combined extracts, papaya leaves and garlic against Candida albicans need to be examined. Purpose: To determine the minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) of combined extracts of papaya leaves and garlic against Candida albicans. Methods: A laboratory experimental study with a post-test control group design was established. The minimum inhibitory concentration was tested using Kirby-bauer method and the minimum fungicidal concentration was tested with agar dilution method. The ratio of each extract in each concentration is 1: 1 which made into five concentrations; 5%, 10%, 15%, 20% and 25%. Results: This study showed the 5%, 10%, 15%, 20%, and 25% extracted of papaya leaves and garlic combination could not inhibit and eliminate Candida albicans colonies. Conclusion: No inhibitory and fungicidal effect of 5%, 10%, 15%, 20% and 25% papaya leaves and garlic extract combination. Higher concentration need to be considered.